UJI DAYA HAMBAT SEDIAAN SABUN CAIR EKSTRAK DAUN PALA (Myristica fragrans houtt) TERHADAP Propionibacterium acnes dan Staphylococcus aureus - Atika Pratiwi; Ella Noorlaela; Siti Mahyuni (Universitas Pakuan, 2019)
Bacteria that cause acne include Staphylococcus aureus and Propionibacterium acnes. Nutmeg leaves are plants that contain antibacterial substances that can inhibit bacterial growth. The purpose of this study is to make soap preparations from nutmeg leaf extracts and find out the formula that is most effective in inhibiting the growth of P.acnes and Staphylococcus aureus bacteria. Nutmeg leaves were extracted using maceration method with 96% ethanol solvent. Liquid soap preparations are made in 4 formulas. Antibacterial activity test was carried out by the dilution method for MIC and disk diffusion methods to determine LDH liquid soap preparations. Based on the test of the antibacterial activity of 96% ethanol extract, nutmeg leaves have the ability to inhibit the growth of Staphylococcus aureus with a MIC value at a concentration of 0.5% and negative on Propionibacterium acnes. Liquid soap preparations in F1 (extract 2%) have LDH values of 9.87 ± 0.41 mm; F2 (extract 4%) has an LDH value of 10.50 ± 0.35 mm; F3 (extract 8%) has an LDH value of 10.70 ± 0.25 mm; F4 (extract 10%) has an LDH value of 11.87 ± 0.25 mm. The highest LDH value is F4 with a concentration of 10% extract, LDH F4 is a formula that has the most antibacterial activity approaching LDH positive control JF Sulfur which has an LDH value of 13.25 ± 0.25 mm